Industrial growth and employment : a regional analysis - Rastogi, Gursharan Bhalla (Jaipur : Rawat Publications, 2011)
Study on the changing pattern of growth and employment in manufacturing sector in India.
Originally presented as the author's thesis (Ph. D.-- Centre for the Study of Regional Development, School of Social Sciences, Jawaharlal Nehru University, New Delhi)
Includes statistical tables.
Includes bibliographical references (p. [199]-204) and index.
Keywords: MANUFACTURING INDUSTRIES -- India; MANUFACTURING INDUSTRIES -- Employees -- Supply and demand -- India